Mengatasi Kesulitan Membuat Jurnal Penutup dengan Metode Inkuiri pada Mata Pelajaran Ekonomi - Sitorus, Nurhayati (Universitas Negeri Medan, 2015)
The subject of this research is 30 students at class Social Science-2 grade XII in SMA 12 of Medan, whilst the object of research is teaching method of inquiry. Whereas the tools of collecting data is score list of student. Based on pre-test to 30 students, resulting 27 students (90 percent) reached lower of learning outcome (not passed) by had not obtained yet 70 score of Minimal Passing Score and 3 students (10 percent) were categorized as passed and obtained 70 of Minimal Passing Score. Then in the first cycle, resulting 12 students (40 percent) were categorized as passed and reached 70 score of minimal, and 18 students (60 percent) were categorized as not passed and had not obtained yet 70 score of minimal.Â In the second cycle, resulting 27 students (90 percent) were categorized as passed and obtained 70 score of minimal, and 3 students (10 percent) were categorized as not passed and had not reached yet 70 score of minimal. Based on result of the research from pre test, post test of both firts and second cycle, there were increasing of learning outcome significantly. Therefore can be concluded that by using method of inquiry, can be elvate learning outcome of students on the subject of Economy on subject matter of Basic Competence in Writing Closing Journal at class Social Science-2 grade XII in SMA 12 of Medan in 2012/2013 school year.